2016
DOI: 10.1007/s10803-016-2831-4
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions in Older Adults With Autism Spectrum Disorder: Objective Performance and Subjective Complaints

Abstract: Although deficits in Executive Functioning (EF) are reported frequently in young individuals with Autism Spectrum Disorders (ASD), they remain relatively unexplored later in life (>50 years). We studied objective performance on EF measures (Tower of London, Zoo map, phonetic/semantic fluency) as well as subjective complaints (self- and proxy reported BRIEF) in 36 ASD and 36 typically developed individuals (n = 72). High functioning older adults with ASD reported EF-impairments in metacognition, but did not dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
80
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 83 publications
12
80
2
1
Order By: Relevance
“…Prior studies have noted that the emergence of anticorrelations between the CEN and the DMN in typical development occurs during a similar developmental window as normative improvements in executive function [e.g., Luna, Garver, Urban, Lazar, & Sweeney, ; Chai et al, ], and stronger anticorrelations between the CEN and DMN are associated with better performance on lab‐based measures of executive function and IQ in neurotypical individuals [Kelly, Uddin, Biswal, Castellanos, & Milham, ; Hampson, Driesen, Roth, Gore, & Constable, ; Sherman et al, ]. Our findings thus suggest the possibility that atypical developmental trajectories between the CEN and DMN in ASD, which prevent them from attaining typical mature patterns of functional connectivity, may be related to the persistent executive function deficits observed in ASD [e.g., Chen et al, ; Davids, Groen, Berg, Tucha, & van Balkom, ; Wang et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have noted that the emergence of anticorrelations between the CEN and the DMN in typical development occurs during a similar developmental window as normative improvements in executive function [e.g., Luna, Garver, Urban, Lazar, & Sweeney, ; Chai et al, ], and stronger anticorrelations between the CEN and DMN are associated with better performance on lab‐based measures of executive function and IQ in neurotypical individuals [Kelly, Uddin, Biswal, Castellanos, & Milham, ; Hampson, Driesen, Roth, Gore, & Constable, ; Sherman et al, ]. Our findings thus suggest the possibility that atypical developmental trajectories between the CEN and DMN in ASD, which prevent them from attaining typical mature patterns of functional connectivity, may be related to the persistent executive function deficits observed in ASD [e.g., Chen et al, ; Davids, Groen, Berg, Tucha, & van Balkom, ; Wang et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ASC participants did report much more cognitive difficulties on a subjective measure as compared to those without ASC (same participants, different paper: van Heijst and Geurts 2015). In a similar study (Davids et al 2016; N ASC = 36, N non-ASC = 36, age 50-84 years), focusing on some of the same cognitive domains, no large differences in performance between the ASC and non-ASC group were observed in neither general processing speed nor planning (although the ASC group was slower) and generativity. Interestingly, ASC participants did report many EF problems in daily life.…”
mentioning
confidence: 83%
“…When including again primarily adults with a late adulthood ASC diagnosis, but now focussing on a much wider age range (N ASC = 118 to, N non-ASC = 118-167 to; 19-79 years; see for detailed findings Lever and Geurts 2016a 2 ; Lever et al 2015Lever et al , 2017 both the larger amount of self-reported cognitive difficulties (similar to Davids et al 2016;van Heijst and Geurts 2015) and EF group differences in generativity (similar to Geurts and Vissers 2012) were replicated. However, no differences emerged between those older adults with and without ASC when using a different WM task (Lever et al 2015, see also Braden et al 2017.…”
mentioning
confidence: 84%
See 2 more Smart Citations